2020
DOI: 10.1521/pedi_2019_33_409
|View full text |Cite
|
Sign up to set email alerts
|

Women With Borderline Personality Disorder Show Reduced Identification of Emotional Facial Expressions and a Heightened Negativity Bias

Abstract: Individuals with borderline personality disorder (BPD) frequently display impairments in the identification of emotional facial expressions paralleled by a negativity bias. However, it remains unclear whether misperception of facial expressions is a key psychopathological marker of BPD. To address this question, the authors examined 43 women diagnosed with BPD and 56 healthy female controls using an emotion face identification task and a face dot-probe task together with measures on psychopathology. Compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 47 publications
(74 reference statements)
2
15
0
Order By: Relevance
“…BPD participants and controls were matched on age (t (52)=0.092; p = .927) and parental education (t (50)= 1.046; p = .300). As previously reported in a larger sample, the BPD participants had a significantly lower educational level (t (51)=3.227; p = .0002), poorer VCI score (t (52)=5.265; p < .0001), and had more self-reported experiences of childhood trauma on the CTQ (t (48)= − 7.502; p < .0001) relative to controls [35,41]. No significant difference between BPD participants and controls was observed in the number of words used to narrate their memories (t (52)=1.096; p = .278).…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…BPD participants and controls were matched on age (t (52)=0.092; p = .927) and parental education (t (50)= 1.046; p = .300). As previously reported in a larger sample, the BPD participants had a significantly lower educational level (t (51)=3.227; p = .0002), poorer VCI score (t (52)=5.265; p < .0001), and had more self-reported experiences of childhood trauma on the CTQ (t (48)= − 7.502; p < .0001) relative to controls [35,41]. No significant difference between BPD participants and controls was observed in the number of words used to narrate their memories (t (52)=1.096; p = .278).…”
Section: Resultssupporting
confidence: 65%
“…We have previously shown that the BPD participants in the present study displayed lower verbal comprehension relative to controls [ 35 , 41 ] and the VCI scale has been shown to be positively associated with reading comprehension and spelling [ 42 ]. Because our participants were asked to write down their autobiographical memories, individual differences in verbal comprehension abilities could affect how the autobiographical memories was communicated on paper.…”
Section: Methodsmentioning
confidence: 85%
“…BPD participants and controls were matched on age (t(52) = 0.092; p = .927) and parental education (t(50) = 1.046; p = .300). As previously reported in a larger sample, the BPD participants had a signi cantly lower educational level (t(51) = 3.227; p = .0002), poorer VCI score (t(52) = 5.265; p < .0001), and had more self-reported experiences of childhood trauma on the CTQ (t(48)=-7.502; p < .0001) relative to controls (35,41). No signi cant difference between BPD participants and controls was observed in the number of words used to narrate their memories (t(52) = 1.096; p = .278).…”
Section: Resultssupporting
confidence: 64%
“…Verbal comprehension index. We have previously shown that the BPD participants in the present study displayed lower verbal comprehension relative to controls (35,41) and the VCI scale has been shown to be positively associated with reading comprehension and spelling (42). Because our participants were asked to write down their autobiographical memories, individual differences in verbal comprehension abilities could affect how the autobiographical memories was communicated on paper.…”
Section: Assessmentsmentioning
confidence: 56%
“…Researchers try to understand the nature of these strong social impairments to improve psychological interventions for BPD. There is extensive research showing that social impairments in BPD are associated with a negativity bias, which means that individuals with BPD process social information in a negative manner [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%